2017
DOI: 10.1152/ajpregu.00169.2017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hindbrain administration of oxytocin is sufficient to elicit weight loss in diet-induced obese rats

Abstract: Oxytocin (OT) administration elicits weight loss in diet-induced obese (DIO) rodents, nonhuman primates, and humans by reducing energy intake and increasing energy expenditure. Although the neurocircuitry underlying these effects remains uncertain, OT neurons in the paraventricular nucleus are positioned to control both energy intake and sympathetic nervous system outflow to interscapular brown adipose tissue (BAT) through projections to the hindbrain nucleus of the solitary tract and spinal cord. The current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
123
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(143 citation statements)
references
References 60 publications
14
123
3
3
Order By: Relevance
“…In HFDinduced obese male and female mice (body fat mass: 36%), 10 days of oxytocin treatment decreased abdominal and subcutaneous fat up to 15-20% without reducing muscle mass [39]. Similar effects of oxytocin on fat mass are found in other studies using HFD-induced obese mice/rats [25,29,31,32] and genetically obese models such as db/db [131] and ob/ob mice [37]. This suggests that the cause of decreased BW induced by oxytocin treatment depends not only on the decreased food intake, but also on the stimulation of lipolysis.…”
Section: Clinical Implications Of Oxytocinsupporting
confidence: 72%
See 1 more Smart Citation
“…In HFDinduced obese male and female mice (body fat mass: 36%), 10 days of oxytocin treatment decreased abdominal and subcutaneous fat up to 15-20% without reducing muscle mass [39]. Similar effects of oxytocin on fat mass are found in other studies using HFD-induced obese mice/rats [25,29,31,32] and genetically obese models such as db/db [131] and ob/ob mice [37]. This suggests that the cause of decreased BW induced by oxytocin treatment depends not only on the decreased food intake, but also on the stimulation of lipolysis.…”
Section: Clinical Implications Of Oxytocinsupporting
confidence: 72%
“…The RQ decrease by oxytocin treatment was also confirmed in rats, monkeys, and humans [25,32,34,35,135]. This reduction of BW by oxytocin may also be mediated by the induction of diet-induced thermogenesis [31,47]. Other factors related to the metabolic disorder were also found to be affected by the oxytocin treatment.…”
Section: Clinical Implications Of Oxytocinmentioning
confidence: 63%
“…130,146,159,160 Oxytocin administration has been shown to reduce food intake in laboratory animals and humans. 164 However, a meta-analysis revealed that the anorexigenic effect of oxytocin administration is not statistically significant in humans. 164 However, a meta-analysis revealed that the anorexigenic effect of oxytocin administration is not statistically significant in humans.…”
Section: Roles Of Oxytocin In the Control Of Food Intakementioning
confidence: 99%
“…[161][162][163] The anorexigenic effect of oxytocin has been shown to be stronger in diet-induced obese rodents. 164 However, a meta-analysis revealed that the anorexigenic effect of oxytocin administration is not statistically significant in humans. 161 SNPs of the gene encoding the oxytocin receptor have been shown to be associated with eating disorders including anorexia nervosa and bulimia nervosa.…”
Section: Roles Of Oxytocin In the Control Of Food Intakementioning
confidence: 99%
“…and into the lateral, third (3V) and fourth ventricle (4V; as a strategy to more specifically target hindbrain OXTRs). Considering the debate over whether peripherally administered OXT crosses the blood‐brain barrier (BBB) and enters the brain in rodents, pigs, sheep, non‐human primates and humans, both the central and peripheral pools of the OXT receptor have been implicated in mediating OXT‐driven hypophagia . In addition, it has been suggested that peripheral OXT may also act, in part, via hindbrain OXTRs: 4V pre‐treatment with an OXTR antagonist attenuated the effects of i.p.…”
Section: Oxytocin and Short‐term Control Of Food Intake: Key Findingsmentioning
confidence: 99%